Does the relationship between health-related quality of life and subjective well-being change over time? An exploratory study among breast cancer patients. (February 2017) - Tessier, Philippe; Blanchin, Myriam; Sébille, Véronique
Abstract: It has been suggested recently that measures of Subjective Well-Being (SWB) instead of preferences could be employed to determine relative weights for the dimensions of health-related quality of life (HRQol) with the aim of developing health utility indexes for economic evaluation purposes. In this context, this paper addresses the possibility of reprioritization response shift in SWB. It examines whether the association between dimensions of HRQol and SWB changes over time in chronically ill patients. 215 women newly diagnosed for breast cancer in a French hospital between 2010 and 2012 completed the Satisfaction with Life Scale (SWLS) and the EORTC QLQ-C30 HRQol questionnaires over a two-year period. We estimated hierarchical random coefficients models for the repeated SWLS measures while allowing for time-varying parameters for the scales of the QLQ-C30 to test for reprioritization. Our findings suggest that women adapt to breast cancer by giving greater weight over time to the social dimension of HRQol. This possibility of reprioritization response shift should be considered in researches trying to develop SWB-based health utility values to inform the allocation of resources in health care. Highlights: Few studies have linked HRQol and subjective well-being (SWB) in patients. Mental health is strongly correlated with the SWB of breast cancer patients. The correlation between the social dimension of HRQol and SWB changes over time. The SWB of breast cancer patients seems to exhibit reprioritization response shift.